2022
DOI: 10.3389/fneur.2022.858439
|View full text |Cite
|
Sign up to set email alerts
|

Associations of chronic diarrheal symptoms and inflammatory bowel disease with sleep quality: A secondary analysis of NHANES 2005–2010

Abstract: ObjectivePoor sleep quality is highly prevalent in patients with chronic diarrheal symptoms or inflammatory bowel disease (IBD). This study aimed to evaluate the associations of chronic diarrheal symptoms and IBD with sleep quality in the general US population.Methods14,696 adults (≥20 years) from the National Health and Nutrition Examination Survey (2005–2010) were included in the study. Chronic diarrheal symptoms and IBD were defined by self-reports. Sleep quality was assessed by sleep disorder, sleep troubl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…However, positive associations were not identified between CD and short sleep, which is most directly related to disrupted circadian rhythms. Surprisingly, when we reviewed the literature, multiple studies reported no correlations between CD and sleep duration ( Elsenbruch et al, 2002 ; Heitkemper et al, 2005 ; Zhang et al, 2022 ). Previous studies investigating the impact of sleep quality on human bowel health also reported contradictory results.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…However, positive associations were not identified between CD and short sleep, which is most directly related to disrupted circadian rhythms. Surprisingly, when we reviewed the literature, multiple studies reported no correlations between CD and sleep duration ( Elsenbruch et al, 2002 ; Heitkemper et al, 2005 ; Zhang et al, 2022 ). Previous studies investigating the impact of sleep quality on human bowel health also reported contradictory results.…”
Section: Discussionmentioning
confidence: 93%
“…This finding was generally consistent with previous studies. For example, Zhang et al (2022 ) found that persons with chronic diarrheal symptoms had higher odds of sleep disorder by 26%. The state of rapid eye movement sleep, arousals, and waking was associated with increased colon motility that may induce the occurrence of diarrhea ( Kim et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bowel leakage on The Bowel Health Questionnaire was used as a proxy for chronic diarrheal Symptoms. Referring to the methodology of previous studies, those with two or more symptoms of bowel leakage [14,15], consisting of gas, mucus, liquid, and solid stool per week, were de ned as having chronic diarrheal symptoms. The questionnaires determined the assessment of IBD, "Ever had Ulcerative Colitis" and "Ever had Crohn's Disease.…”
Section: Chronic Diarrheal Symptoms and Ibdmentioning
confidence: 99%
“…Poor sleep quality leads to a decline in both physical and psychological well-being, resulting in symptoms like fatigue, anxiety, and stress [8,9]. Chronic disease is one of the factors that associated with poor sleep quality [10][11][12].…”
Section: Introductionmentioning
confidence: 99%